Pembangunan Sistem Aplikasi Hanasu : Pembelajaran Bahasa Jepang Android Mobile Memanfaatkan Google Speech Recognition Library - Eko Prasetyo Lukman Nur Hakim; Komang Candra Brata; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Indonesia has many populations which have the interest to learn the Japanese Language under China.Meanwhile in Indonesia Japanese Language only can be learned in school or Japanese course place,it makes so many people who want and interest to learn the Japanese Language they do it bythemselves. The Japan Foundation Jakarta said that facilities and services in Indonesia are not goodenough for study or even the study method. But in this globalization era is possible to learn theJapanese Language in everywhere such as website, e-book, or applications that available on thesmartphone. Google speech-to-text library is a library which provided by Google for making the usercould speak over their smartphone and process it to become text. By using this technology, theapplication created which could learn the Japanese Language by talking some vocabulary orsentences in Japanese Language, after that system will check the rightness. The system that includeswith features that fit with the requirements, implemented with a database, and implemented using Javaand XML. This Japanese Language learning has been successfully tested using a black box testingmethod on validation testing, A/B Testing on usability testing and post-test only design study forperformance testing that is this system could improve study method over study method using books.The result is study from Hanasu apps is more efficient than study from books.